“De nuevo sobre artículo + posesivo + sustantivo. Textos vizcaínos de los siglos XV-XVIII - Gómez Seibane, Sara (El Colegio de México, 2010)
In the present research, the author argues the chronological disappearanceof the Spanish article + possessive structure in Biscay’s (Spain) administrativedocuments, what it has been semantically characterized followingsome related works by Concepción Company. First, the loss of the definitearticle + possessive structure has been documented by 18th century, whereasthe indefinite article does not go further than the first quarter of 16thcentury. In addition, the possessor accessibility through the possessum, aswell as the possessum actualization and modification, depending on thepossessor. Finally, the results provide strong support for the connectionbetween the indefinite article + possessive construction and the un article likegrammaticalization.